Identifying the critical period for waterlogging on yield and its components in wheat and barley - de San Celedonio, Romina Paola (2014)
Background and aims Crop tolerance to waterlogging depends on factors such as species sensitivity and the stage of development that waterlogging occurs. The aim of this study was to identify the critical period for waterlogging on grain yield and its components, when applied during different stages of crop development in wheat and barley. Methods Two experiments were carried out (E1: early sowing date, under greenhouse; E2: late sowing date, under natural conditions). Waterlogging was imposed during 15-20 days in 5 consecutive periods during the crop cycle (from Leaf 1 emergence to maturity). Results The greatest yield penalties occurred when waterlogging was applied from Leaf 7 appearance on the main stem to anthesis (from 34 to 92% of losses in wheat, and from 40 to 79% in barley for E1 and E2 respectively). Waterlogging during grain filling reduced yield to a lesser degree. In wheat, reductions in grain number were mostly explained by reduced grain number per spike while in barley, by variations in the number of spikes per plant. Conclusions The time around anthesis was identified as the most susceptible period to waterlogging in wheat and barley. Exposing the crop to more stressful conditions, e.g. delaying sowing date, magnified the negative responses to waterlogging, although the most sensitive stage (around anthesis) remained unchanged.